Mapping the Global Landscape of Export Readiness: A Two-Decade Bibliometric Analysis - Hasnin, Hannisa; Riani, Desmy; Kuraesin, Ecin; Syahdiany, Geny (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2025)
This study examines the evolving landscape of export readiness through a hybrid approach combining Bibliometric Analysis and a Systematic Literature Review (SLR). Utilizing data from the Scopus database spanning the period from 2005 to 2025, the research identifies 97 relevant scientific articles through the rigorous PRISMA protocol. Analysis was conducted using Biblioshiny and VOSviewer to map authorship networks, citation trends, and thematic clusters. Findings reveal a steady 15.22% annual growth in research interest, with institutions such as North-West University and the University of Wisconsin-Madison emerging as leading contributors. Thematic mapping highlights a transition from traditional themes like export performance and general economics toward emerging concerns such as digital adoption, structural reforms, and decision-making processes. The results pinpoint a significant research gap: the lack of interconnection between export readiness, advanced technology, and institutional governance, particularly within developing economies. This study provides a comprehensive knowledge map that serves as a foundation for future researchers and policymakers to develop more integrated frameworks for internationalization.